Intestinal parasites and diabetes: A systematic review and meta-analysis. (January 2023) - Zibaei, Mohammad; Bahadory, Saeed; Saadati, Hassan; Pourrostami, Kumars; Firoozeh, Farzaneh; Foroutan, Masoud
Abstract: Background: Investigating the association between infectious agents and non-communicable diseases is an interesting emerging field of research. Intestinal parasites (IPs) are one of the causes of gastrointestinal complications, malnutrition, growth retardation and disturbances in host metabolism, which can play a potential role in metabolic diseases such as diabetes. The aim of the present study was to investigate the prevalence of IPs in diabetic patients and the association between IPs and diabetes. Methods: A systematic literature search was conducted from January 2000 to November 2022in published records by using PubMed, Scopus, and Web of Science databases as well as Google scholar search engine; Out of a total of 29 included studies, fourteen cross-sectional studies (2676 diabetic subjects) and 15 case-control studies (5478 diabetic/non-diabetic subjects) were reviewed. The pooled prevalence of IPs in diabetics and the Odds Ratio (OR) were evaluated by CMA V2. Results: In the current systematic review and meta-analysis, the pooled prevalence of IPs in diabetic patients was 26.5% (95% CI: 21.8–31.7%) with heterogeneity of I 2  = 93.24%; P  < 0.001. The highest prevalence based on geographical area was in Region of the Americas (13.3% (95% CI: 9.6–18.0)).There was significant association between the prevalence of intestinal parasites in diabetic cases compared to controls (OR, 1.72; 95% CI: 1.06–2.78). Conclusion: In line with the high prevalence of IPs in diabetic patients, significant association was found however, due to the limitations of the study, more studies should be conducted in developing countries and, the prevalence of IPs in diabetics should not be neglected.